Bridging the Gap: The Intersection of Nursing and Pharmacy in Comprehensive Healthcare Delivery - Hanadi Abdulrazaq Mohammed Almasnid,; Ahmed Dakhilallah Alzahrani,; Abdullah ibrahim raja alotaibi,; Motebmauoyf Alqorashi,; Hani Mohammed Dakhil ALthaqafi,; Jaber Mohammed Ali Majrashi,; Nour Homoud abdullah alanazi,; Abdulaziz Saud Jihad Al-Anazi,; Majed Muhammad Radi Al-Sarihi,; Meshari Bashir Rabea Alrashidi,; Mohammed Nasser musfer alqahtani,; Majid Abdallah Alzahrani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Interprofessional collaboration has emerged as a critical imperative in healthcare to address rising patient complexity, ensure care continuity, and optimize outcomes. At the forefront of this paradigm shift is the synergistic partnership between nursing and pharmacy - two pivotal professions whose complementary expertise intersects profoundly in medication safety, chronic disease management, and holistic patient care. This paper examines the multifaceted benefits and challenges of nurse-pharmacist collaboration through an integrative review of literature and global policy frameworks. The profound impact of interprofessional education (IPE) in cultivating a collaborative mindset is explored, alongside strategies for overcoming barriers spanning siloed education, hierarchical structures, resistant organizational cultures, and fragmented health information systems. Comprehensive recommendations are provided, encompassing curricula reform, collaborative practice models, role delineation, psychological safety, health IT solutions, resource allocation, and alignment with accreditation standards. By capitalizing on the synergies between nursing and pharmacy through robust interprofessional collaboration, healthcare organizations can unlock the full potential of patient-centered, high-quality care delivery. This integrated approach aligns with the Quadruple Aim of enhancing patient experiences, improving population health, reducing costs, and promoting provider well-being. Ultimately, this paper underscores the pivotal role of nurse-pharmacist partnerships in driving transformative change towards seamless, coordinated healthcare.